2016
DOI: 10.1038/emm.2016.31
|View full text |Cite
|
Sign up to set email alerts
|

F-box only protein 9 is an E3 ubiquitin ligase of PPARγ

Abstract: Peroxisome proliferator-activated receptor gamma (PPARγ) is a critical regulator of carbohydrate and lipid metabolism, adipocyte differentiation and inflammatory response. Post-translational modification of PPARγ and its degradation involve several pathways, including the ubiquitin–proteasome system. Here, we identified F-box only protein 9 (FBXO9) as an E3 ubiquitin ligase of PPARγ. We screened interacting partners of PPARγ using immunoprecipitation and mass spectrometric analysis and identified FBXO9 as an E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…The genes mapped by these sites were reported to be closely associated with multiple metabolic diseases (Table 5). For instance, SQSTM1 and FBXO9 were related with diabetes mellitus [32, 33]. GRWD1 and ATP10A were involved with insulin resistance [34-36].…”
Section: Resultsmentioning
confidence: 99%
“…The genes mapped by these sites were reported to be closely associated with multiple metabolic diseases (Table 5). For instance, SQSTM1 and FBXO9 were related with diabetes mellitus [32, 33]. GRWD1 and ATP10A were involved with insulin resistance [34-36].…”
Section: Resultsmentioning
confidence: 99%
“…In parallel, the Shh/Smo/ERK axis decreased the PPAR␥ protein level. Furthermore, the E3 ubiquitin ligases, CUL4B, FBXO9, MuRF2, MuRF3, and Siah2 regulate PPAR␥ ubiquitination in adipocytes, thus decreasing adipogenesis and lipogenesis (40,(43)(44)(45)(46). Other E3 ligases, such as MKRN1 and MDM2, are also involved in PPAR␥ ubiquitination and proteasome-dependent degradation (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…We generated a mutant form of Fbxo9 lacking the F-box motif (Fbxo9ΔF; Fig. 7A), which is able to bind to its substrates without inducing ubiquitination (22). As expected, expression of Neurog2 protein persisted in Sox10 + cells overexpressing Fbxo9ΔF in the DRG, whereas Neurog2 was barely detectable in the vector control (Fig.…”
Section: Overexpression Of Fbxo9 Mutant Stabilizes Neurog2 Protein Andmentioning
confidence: 74%
“…It has been shown that Fbxo9 is augmented in human coronary arterial smooth muscle cells under high glucose culture and in the vessels of streptozotocin-induced diabetic rat, leading to UPS-mediated BK-β 1 degradation. In addition, Fbxo9 was shown to be required for adipocyte differentiation through modulating the level of peroxisome proliferator-activated receptor gamma protein (21,22). Another study showed that, in response to growth factor deprivation, Fbxo9-mediated ubiquitination of telomere maintenance 2 (Tel2) and Tel2 interacting protein 1 (Tti1) inactivated mTORC1, but activated the PI(3)K/TORC2/ Akt pathway to promote survival in multiple myeloma (23).…”
Section: Significancementioning
confidence: 99%